Engineering strategies for rational polyketide synthase design. Issue 10 (25th June 2018) - Klaus, Maja; Grininger, Martin
Abstract : In this review, we highlight strategies in engineering polyketide synthases (PKSs). We focus on important protein–protein interactions that constitute an intact PKS assembly line. Abstract : Covering: mid 1990s to 2018 Over the last two decades, diverse approaches have been explored to generate new polyketides by engineering polyketide synthases (PKSs). Although it has been proven possible to produce new compounds by designed PKSs, engineering strategies failed to make polyketides available via widely applicable rules and protocols. Still, organic synthetic routes have to be employed whenever new polyketides are needed for applications in medicine, agriculture, and industry. In light of the rising demand for commodity products from feedstock and for fast and cheap access to pharmaceutical compounds, the need for harnessing PKSs to produce such molecules is more urgent than ever before. In this review, we focus on a multitude of approaches to engineer modular PKSs by swapping and replacing PKS modules and domains, which we analyze in the light of recent structural and biochemical data. We conclude with an outlook on possible strategies on how to increase success rates of PKS engineering in future.